2020
DOI: 10.3390/ijerph17176137
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Superspreading Events in 2015 MERS-CoV Outbreak in Korea by Branching Process Models

Abstract: South Korea has learned a valuable lesson from the Middle East respiratory syndrome (MERS) coronavirus outbreak in 2015. The 2015 MERS-CoV outbreak in Korea was the largest outbreak outside the Middle Eastern countries and was characterized as a nosocomial infection and a superspreading event. To assess the characteristics of a super spreading event, we specifically analyze the behaviors and epidemiological features of superspreaders. Furthermore, we employ a branching process model to understand a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The characteristics of the selected articles are listed in Supplementary Table S3 . Among the 60 estimates of transmission heterogeneity, four (6.7%) from two studies estimated the dispersion parameter ( k ) of SARS [16] , [18] , 11 (18.3%) from eight articles estimated the k for MERS [16] , [17] , [30] , [31] , [32] , [33] , [34] , [35] , and 45 (75.0%) from 17 articles estimated the k for COVID-19 [14] , [15] , [19] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] . Forty estimates (66.7%) were based on transmission pair data (i.e., offspring case number generated by each index case), and four estimates were calculated using epidemic/cluster size data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the selected articles are listed in Supplementary Table S3 . Among the 60 estimates of transmission heterogeneity, four (6.7%) from two studies estimated the dispersion parameter ( k ) of SARS [16] , [18] , 11 (18.3%) from eight articles estimated the k for MERS [16] , [17] , [30] , [31] , [32] , [33] , [34] , [35] , and 45 (75.0%) from 17 articles estimated the k for COVID-19 [14] , [15] , [19] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] . Forty estimates (66.7%) were based on transmission pair data (i.e., offspring case number generated by each index case), and four estimates were calculated using epidemic/cluster size data.…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, standard compartment models (e.g., the classic susceptible-infectious-recovered model) were combined with superspreading compartments to characterize the transmission heterogeneity of SARS [12] and MERS outbreaks [13] . In contrast, some studies [14] , [15] , [16] , [17] fitted the observed epidemiological data by a negative binomial (NB) distribution to quantify the superspreading potential. This approach was initially proposed by Lloyd-Smith et al [18] , in which the heterogeneity of infectiousness among individuals was quantified by estimating the dispersion parameter ( k ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This clearly showed super-spreading events (the five super-spreaders) in generating secondary cases due to various complex factors. More detailed epidemiological data on the 2015 MERS-CoV cases can be found in the previous studies [23,24].…”
Section: Generating the Simulation Space Based On The Empirical Contamentioning
confidence: 99%
“…The infection spread is largely due to superspreaders in the community who transmit the infection to several individuals, [18] these cases can only be prevented by detailed network analysis. [19] Thus, it is very important to post-process the contact tracing data, and make strategies for testing and isolating individuals at the risk. Policymakers should have strategies to acquire maximum spread information using minimum tests conducted in the community.…”
Section: Introductionmentioning
confidence: 99%